Disease-specific Growth Charts of Marfan Syndrome Patients in Korea - Kwun, Younghee (J Korean Med Sci, 2015)
Patients with Marfan syndrome (MFS) presents with primary skeletal manifestations such as tall stature, chest wall abnormality, and scoliosis. These primary skeletal manifestations affect the growth pattern in MFS. Therefore, it is not appropriate to use normal growth charts to evaluate the growth status of MFS. We aimed to develop disease-specific growth charts for Korean MFS patients and to use these growth charts for understanding the growth patterns in MFS and managing of patients with MFS. Anthropometric data were available from 187 males and 152 females with MFS through a retrospective review of medical records. Disease-specific growth charts were generated and 3, 25, 50, 75, and 97 percentiles were calculated using the LMS (refers to λ, μ, and σ, respectively) smoothing procedure for height and weight. Comparisons between MFS patients and the general population were performed using a one-sample t-test. With regard to the height, the 50th percentile of MFS is above the normative 97th percentile in both genders. With regard to the weight, the 50 percentile of MFS is above the normative 75th percentile in male and between the normative 50th percentile and the 75th percentile in female. The disease-specific growth charts for Korean patients with MFS can be useful for monitoring growth patterns, planning the timing of growth-reductive therapy, predicting adult height and recording responses to growth-reductive therapy.